THE IMPLEMENTATION OF PROBLEM BASED LEARNING ACTIVITY THROUGH ONLINE SCHOOL FIELD PRACTICE - Budiarti Putri Uleng; Nadya Nurhidayah Nurdin (LPPM Institut Pendidikan Nusantara Global, 2023)
The application of problem-based learning is a style of methodology that puts the idea of learning from facts and looking at real-world problems into practice. In order to examine mediated communication, this study used a qualitative ex experimental design using qualitative techniques. This method, known as the